PENGARUH PENERAPAN MARKETING MIX (4P) TERHADAP VOLUME PENJUALAN PRODUK MIE JEBEW PAK DAYAT JEMBER - Amaliya, Yeni; Nursaid, Nursaid; Qomariah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This research aims to analyze in depth the marketing strategy implemented by Mie Jebew Pak Dayat in Jember using the 4P marketing mix concept, which includes product, price, location and promotion elements. In an effort to understand the implementation of this marketing strategy, this research uses interviews and direct observation methods with restaurant owners and staff. The analysis results show that Mie Jebew Pak Dayat has succeeded in offering high quality products, especially noodles with a distinctive spicy taste which has been proven to meet the tastes of the local market. Apart from that, the prices offered are quite competitive, comparable to the quality of the products provided, and can compete amidst the many other culinary businesses. Even though this restaurant is located in a strategic location in the center of Jember city, this research found that the restaurant's visibility could still be improved by adding more attractive ornaments and lighting to the outside of the restaurant to make it easier for customers to find the place. In terms of promotion, Mie Jebew Pak Dayat has succeeded in utilizing social media such as Instagram and Facebook as the main channels to build awareness and introduce their products to a wider audience. Word of mouth also plays an important role, with satisfied customers sharing their positive experiences on social media and in everyday conversations, strengthening the restaurant's brand image. It is hoped that the results of this research will provide broader insight for culinary entrepreneurs in designing marketing strategies that are more effective and adaptive to market changes, as well as becoming a reference in increasing the competitiveness of culinary businesses in this era of globalization.